Juvenile Delinquency in Bangladesh: Identifying the causes with prevention and rehabilitation - Islam, Md. Tajul (Technium Social Sciences Journal, 2021)
Juvenile Delinquency has grown to be one of the major discussing issues at present world. This study has attempted to focus on Juvenile Delinquency in Bangladesh. This study has also attempted to investigate the causes, prevention and rehabilitation of this Juvenile Delinquency. This study has been carrying out from June 2020 to January 2021. Using secondary data, this paper attempted to look at the reasons of Juvenile Delinquency and its impact on the society in Bangladesh. Several reports on Juvenile Delinquency, journals, articles, research papers were the sources of data. More than 5 Juvenile Delinquents were selected for collecting the supporting data through in-depth interview. As the study was qualitative based, the data were analyzed in descriptive and contextual methods. The findings of this study have revealed that there is a number of reasons of Juvenile Delinquency and this Juvenile Delinquency have a great impact on the causation of crime in a society at large of the country. Thus, this study has provided insightful information about the causes, prevention and treatment of Juvenile Delinquency in Bangladesh which might help the future researchers in the field of Juvenile Delinquency and its control to policy makers of this target group.